Direct Cost of Parkinson’s Disease: A Real-World Data Study of Second-Line Therapies - Elisa Gomez-Inhiesto; María Teresa Acaiturri-Ayesta; Iker Ustarroz-Aguirre; Diana Camahuali; Maider Urtaran-Laresgoiti; Marisol Basabe-Aldecoa; Roberto Nuño-Solinís; Elena Urizar (Parkinson's Disease)
Parkinson’s disease is one of the main reasons for neurological consultation in Spain. Due to the nature of the disease, it impacts patients, families, and caregivers. Parkinson’s disease is a degenerative disease with no cure, although second-line therapies have recently improved the quality of life of patients in advanced stages. The aim of this study was to analyse the costs of the following therapies: deep brain stimulation (DBS), continuous duodenal levodopa/carbidopa infusion (CDLCI), and continuous subcutaneous apomorphine infusion (CSAI). The methodology used was based on real-world data obtained from an integrated healthcare organization in the Basque Country from 2016 to 2018. This bottom-up retrospective approach only took into account the healthcare perspective. The results revealed the annual cost over 3 years and the projected cost for an additional 2 years. The total costs for 5 years of treatment were as follows: €53,217 for DBS, €208,163 for CDLCI, and €170,591 for CSAI. These costs are in line with those found in the available literature on the subject. Additionally, the analysis provided details of the different costs incurred during intervention with the therapies and compared the costs to those reported in other studies.